The Nondimensionalization of Equations Describing Enzymatic Cellulose Hydrolysis - Norazaliza, Mohd Jamil; Qi, Wang (IDOSI Publication, 2016)
The enzymatic hydrolysis is a very crucial stage in transforming lignocellulosic biomass to bioethanol. At the hydrolysis stage, two types of enzymes, which are EG and CBH , break the cellulose chains 1 1 into sugar in the form of cellobiose or glucose. This paper explores the current kinetic model for enzymatic hydrolysis. The complexity of the model due to integro-differential equations makes finding the analytical solution difficult. Therefore, we divide the full model into two limiting cases and perform mathematical analysis for both cases. Through the use of nondimensional numbers, the governing equations of the kinetic model are summarized. Then, the approximate solutions were derived by utilizing the asymptotic analysis method. Some significant characteristics are captured. It is shown that the number of cellulose chains in both models increases over time due to the effect of enzymes in breaking the cellulose chains into smaller chains. Also, the rate coefficient for CBH to locate and thread a reducing end of a cellulose chain is a key factor in bioconversion.